Simetria de Lie de uma equação KdV com dispersão não-linear - Sousa, Poliane Lima de (2015)
The Rosenau-Hyman, or K(m, n), equations are a generalized version of the Korteweg-de Vries (KdV) equation where the dipersive term is non-linear. Such partial differential equations not always have a specific method by which can be solved, besides the solutions are not always analytical. The Lie symmetry method was applied to look for solutions of these equations. This method consists in finding the most general symmetry group of the equation, wherewith the solution can be found. It was found an expression to the solution and to some particular cases. It was shown that in the case K(2, 2) a new kind of solution, called compacton, with peculiar properties is found.